Pengaruh Penggunaan Tepung Biji Kecipir (Psophocarpus Tetragonolobus L.) Sebagai Substitusi Tepung Beras Dalam Pembuatan Kue Apem Terhadap Kadar Protein Dan Daya Terima - Saputro, Dwi, Pramudya Kurnia, STP., M.Agr (2016)
THE IMPACT OF USING WINGED BEAN FLOUR (Psophocarpus tetragonolobus L.) AS A SUBSTITUTION OF RICE FLOUR IN MAKING APEM CAKE TO THE CONCENTRATION OF PROTEIN AND RECEPTIVITY Introduction : The highest nutrients content of apem cake is carbohydrate (39,55 %), because of the main ingredient for making apem cake is rice flour. Winged bean contain high protein that is 33,3-38.3% in the old seed, however utilization of winged bean plants still limited and not yet optimized. To increase nutrients content especially protein in the apem cake can using winged bean flour that substituted with rice flour. Purpose : This research aims to know the protein content and receptivity of apem cake that making from substitution of winged bean flour. Research methods : The kind of research is experiment. The planning of research is using random complete plan have three treatments and one control with two times repeatition. The substitution of winged bean flour are 0%, 5%, 10%, and 15%. Protein content getting from using semimicro Kjeldahl methods and receptivity getting from joy test of 30 panelists. The statistic test with Anova to continued Duncan test. Result : The result of Anova indicate that value of p value protein content is 0,023. The result of Anova indicate that value of p value receptivity in apem cake of colour is 0,712 ; 0,437 of flavor ; 0,015 of taste ; 0,975 of texture , and overall 0,202. Conclusion : There is difference or an influence from apem cake with substitution of winged bean flour from protein content and taste, however isn't influence on colour, flavor, texture, and whole. Suggestion : On furthermore research about making apem cake with subtitution of receptivity it should using panelists that aggregate of more than 30 people if using consumer and to attention of process or the winged bean flour process so that to cause the loss of special flavor in peanut (beany flavor) and beany after taste. Keywords : winged bean flour, protein content, receptivity, apem cake Bibliography : 60 : 1985-2014